Performance of cutting nanofluids in tribological testing and conventional drilling. (January 2017) - Mosleh, Mohsen; Ghaderi, Mohamad; Shirvani, Khosro A.; Belk, John; Grzina, Donald J.
Abstract: Extreme pressure (EP) testing of cutting fluids modified by diamond and molybdenum disulfide (MoS2 ) nanoparticles were carried out as a possible predictor of behavior of these fluids when used in conventional drilling. EP tests showed that nanofluids containing 2–4% MoS2 nanoparticles increased the load carrying capacity up to 16% while significantly reducing the transfer of material from the softer stainless steel balls to the harder tungsten carbide ball. In contrast, nanofluids containing up to 1% diamond nanoparticles reduced the load carrying capacity by 10%. In conventional drilling tests, the MoS2 nanofluid exhibited 25% longer drill bit service life and a steadier and lower cutting force and torque. Also, the built-up edge (BUE) on the drill bits tested with nanofluids containing MoS2 nanoparticles was easily scraped off from the cutting edges. Dispersion of diamond nanoparticles in the baseline fluid did not enhance the machining performance in drilling tests.